EDUKASI ETIKA BERKUNJUNG DI KAWASAN WISATA RELIGI MASJID RAYA AL JABBAR BANDUNG - Riffka Fauzany; Hani Hatimatunnisani; Nita Rustanti; Ayulia Nirwani (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2026)
Religious tourism is an important sector that contributes to strengthening religious values while supporting local economic development. As one of the prominent religious tourism destinations in West Java, Masjid Raya Al Jabbar attracts a large number of visitors with diverse backgrounds. However, not all visitors fully understand the ethics of visiting a place of worship, including maintaining cleanliness, respecting worship activities, and preserving public facilities. This community service activity aimed to improve visitors' understanding of proper etiquette in religious tourism through field observation, brief educational sessions, interactive discussions, and the dissemination of educational information. The activity involved visitors at the Masjid Raya Al Jabbar area and emphasized the importance of responsible behavior during visits. The results indicated an increased awareness among participants regarding cleanliness, orderliness, respect for religious values, and the proper use of public facilities. Participants also demonstrated a better understanding of the mosque's role as a center for worship, education, and community empowerment. This activity is expected to encourage responsible visitor behavior and support the sustainable management of religious tourism destinations through collaboration between visitors, the local community, and destination managers. Keywords: religious tourism; visitor etiquette; community service; visitor education; Masjid Raya Al Jabbar.